HASHIMOTO’S THYROIDITIS HYPERTHYROID STAGE - Hapsari, Siti Nurul; Soehita, Sidarti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Preliminary: Hashimoto thyroiditis (chronic autoimmune thyroiditis) is the most common cause of hypothyroidism in iodine- sufficient areas of the world, but can sometimes show hyperthyroidism. Case: A 39-year-old female was referred due to shortness of breath and tremor, four hours before hospitalization. There was nausea, chest pain, cold chills and palpitation. She was diagnosed with Hashimoto?s thyroiditis and routinely received tyrosol, propanolol and dexamethasone. Physical examination: cervical mass, afebrile, blood pressure 130/70 mmHg, pulse rate 110 x/minute and respiratory rate 20 x /minute. Laboratory examinations showed WBC 7.53 x 109/L, Hb 11.0 g/dL and platelet count 168 x 109/L. Chest X-Ray: negative for infiltrates. Several laboratory tests were performed, abnormal results were as follows: FT4 2.96 ng/dL (increased), TSH 0.003 uIU/mL (decreased), anti-TPO (antithyroid microsomal antibody) 306 IU/ml (increased), Ig E 213.6 IU/mL (increased). Peripheral blood smear, coagulation test, serum electrolytes, liver function tests, renal function tests, urinalysis, CEA and Ca 125 were within normal limits. A thyroid ultrasound resulted in a benign lesion. Fine Needle Aspiration Biopsy concluded in lymphocytic Hashimoto?s thyroiditis. Echocardiography showed hyperthyroid heart disease. Discussion: Due to an increase in anti-TPO and FT4, a decrease in TSH and lymphocytic thyroiditis from FNAB, this patient was diagnosed with Hashimoto?s Thyroiditis Hyperthyroid Stage. Conclusion: Thyroid function tests and thyroid antibody tests must be monitored to decide whether it is hyperthyroid or hypothyroid stage of Hashimoto thyroiditis.